Pathogenesis of Cardiomyopathy Caused by Variants in ALPK3, an Essential Pseudokinase in the Cardiomyocyte Nucleus and Sarcomere. Issue 22 (2nd November 2022) - Agarwal, Radhika; Wakimoto, Hiroko; Paulo, Joao A.; Zhang, Qi; Reichart, Daniel; Toepfer, Christopher; Sharma, Arun; Tai, Angela C.; Lun, Mingyue; Gorham, Joshua; DePalma, Steven R.; Gygi, Steven P.; et al.
Abstract : Background: ALPK3 encodes α-kinase 3, a muscle-specific protein of unknown function. ALPK3 loss-of-function variants cause cardiomyopathy with distinctive clinical manifestations in both children and adults, but the molecular functions of ALPK3 remain poorly understood. Methods: We explored the putative kinase activity of ALPK3 and the consequences of damaging variants using isogenic human induced pluripotent stem cell–derived cardiomyocytes, mice, and human patient tissues. Results: Multiple sequence alignment of all human α-kinase domains and their orthologs revealed 4 conserved residues that were variant only in ALPK3, demonstrating evolutionary divergence of the ALPK3 α-kinase domain sequence. Phosphoproteomic evaluation of both ALPK3 kinase domain inhibition and overexpression failed to detect significant changes in catalytic activity, establishing ALPK3 as a pseudokinase. Investigations into alternative functions revealed that ALPK3 colocalized with myomesin proteins (MYOM1, MYOM2) at both the nuclear envelope and the sarcomere M-band. ALPK3 loss-of-function variants caused myomesin proteins to mislocalize and also dysregulated several additional M-band proteins involved in sarcomere protein turnover, which ultimately impaired cardiomyocyte structure and function. Conclusions: ALPK3 is an essential cardiac pseudokinase that inserts in the nuclear envelope and the sarcomere M-band. Loss of ALPK3 causes mislocalization of myomesins, critical force-buffering proteins in cardiomyocytes, and also dysregulates M-band proteins necessary for sarcomere protein turnover. We conclude that ALPK3 cardiomyopathy induces ventricular dilatation caused by insufficient myomesin-mediated force buffering and hypertrophy by impairment of sarcomere proteostasis.